SOCIAL MEDIA MARKETING SEBAGAI SARANA PENGEMBANGAN KEWIRAUSAHAAN BERBASIS SOCIO-TECHNOPRENEURSHIP DI UNIVERSITAS ISLAM RIAU - Benni Handayani; Fatmawati Moekahar; Yudi Daherman; Mufti Hasan Alfani (Jurnal Riset Komunikasi (JURKOM), 2020)
Creative business in the last few decades has experienced growth supported by technological advancements. This phenomenon is then commodified using a social approach. The above model is known as Socio-technopreneurship. This study discusses social media marketing as marketing media and social media by utilizing technology in building brand awareness of the 5 types of businesses including unaware of brand, brand recognition, brand recall, and top of mind, supporting students, this research is centered in the business center floating canteen of the Riau Islamic University that accommodates a variety of young entrepreneurs both students and alumni with forms of business in any field both goods and services. This research uses a descriptive qualitative approach, collecting data through observation, interviews, and documentation. The conclusion was that social media management competencies especially Instagram used by informants for business media tend to be conventional, even though the latest trends in the online business world are increasingly dynamic and varied. The development of Socio-technopreneurship eventually becomes a significant method in an effort to improve the above competencies.